Elements Distribution in Soil and Plants of an Old Copper Slag Dump in the Middle Urals, Russia - Zolotova, Ekaterina; Ryabinin, Viktor (Ecological Questions, 2019)
The elements concentration in soil and accumulation in plants growing spontaneously on an old copper slag dump were studied. The research object was a landfill site of the Polevskoy copper smelter (Middle Ural, Russia), which is about 200 years old. We investigated composite samples, consisting of soil blocks (20 x 20 cm) with growing plants. Samples were selected on a transect of 4–5 m at equal intervals. The composite sample was divided into slag fractions: stone, gravel, fine soil (particles smaller than 1 mm); plant fractions: moss and roots, stems and leaves. The microelement analysis of the samples was carried out at an analytical center of the Institute of Geology and Geochemistry, Ural Branch of RAS. The analyses were performed by inductively coupled plasma mass-spectrometry using Elan-9000 ICP massspectrometer. The formation of technogenic soil with a thickness of 10–15 cm on the dump of cast copper slag has begun two hundred years ago. Fine soil constitutes more than one third of the technogenic soil mass and acts as a sorption geochemical barrier. Fine soil accumulates elements mobilized from slag. The concentration of most elements in fine soil is 1–2 orders of magnitude higher than their concentration in slag stone. Pb, Cd, Bi are particularly effectively retained in fine soil: their content is 700-1000 times higher than in slag stone. In the conditions of unlimited supply of elements released from slag, plant reaches the upper threshold of accumulation. The aboveground plant parts compared to litter (roots and moss) have a lower concentration of all elements, but they show the stronger ability to accumulate selenium.